Separation of isobaric phosphorothioate oligonucleotides in capillary electrophoresis: study of the influence of cationic cyclodextrins on chemo and stereoselectivity - Ghassemi, Maryam K.; Hurlet, Vincent; Crommen, Jacques; Servais, Anne-Catherine; Fillet, Marianne (Frontiers in Analytical Science, 2024)
Phosphorothioate (PS) oligonucleotides have drawn more and more attention lately due to their great therapeutic potential. The presence of one (or several) phosphorothioate moiety (ies) improves pharmacokinetic properties but at the same time creates an additional chiral center for each phosphorothioate linkage, and thus diastereomers. It is therefore important to develop analytical strategies to monitor individual species to enable more in-depth investigations. In this study, a PVA coated capillary with a background electrolyte made of 100 mM phosphoric acid adjusted to pH 3.0 with triethanolamine was used. A design of experimental approach provides the optimal conditions for the separation of the eight isobaric diastereomers bearing one phosphorothioate linkage (Mix 1), and the separation of the 12 isobaric diastereomers of a mixture made of oligonucleotides with two phosphorothioate linkages (Mix 2). Remarkably, full separation in Mix 1 could be achieved using a combination of a cationic cyclodextrin (2-hydroxy-3-N,N,N-trimethylamino) propyl-γ-CD chloride, and an anionic cyclodextrin (carboxymethyl-β-cyclodextrin sodium salt), while a second cationic cyclodextrin (2-hydroxy-3-N,N,N-trimethylamino) propyl-β-CD chloride) was required for Mix 2, providing additional selectivity.